Shadows of the rising sun : - Taylor, Jared (Charles E. Tuttle Co., Inc., 1983)
Part 1: chapter 1 Uniqueness, chapter 2 Hierarchy, chapter 3 The group, chapter 4 Conformity, chapter 5 Reason, feeling, and religion